2015
DOI: 10.1111/jav.00673
|View full text |Cite
|
Sign up to set email alerts
|

No change in common cuckooCuculus canorusparasitism and great reed warblers’Acrocephalus arundinaceusegg rejection after seven decades

Abstract: The coevolutionary process among avian brood parasites and their hosts involves stepwise changes induced by the antagonistic selection pressures of one on the other. As long‐term data on an evolutionary scale is almost impossible to obtain, most studies can only show snapshots of such processes. Information on host behaviour, such as changes in egg rejection rates and the methods of rejection are scarce. In Hungary there is an interesting case between the common cuckoo Cuculus canorus and the great reed warble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…50%; Moskát 143 & Honza, 2002;Zölei et al, 2015). Great reed warblers breed in reed beds grown on both sides 144 of small channels.…”
mentioning
confidence: 99%
“…50%; Moskát 143 & Honza, 2002;Zölei et al, 2015). Great reed warblers breed in reed beds grown on both sides 144 of small channels.…”
mentioning
confidence: 99%
“…As we defined mimicry as the difference between host and parasitic eggs, this suggests that 268 mimicry was improving with time. Interestingly, a recent study on cuckoos and great reed warblers in Hungary pointed to the 286 stability of this host-brood parasitic relationship regarding parasitism rate and hosts' responses 287 to parasitism in the last 70 years (Zölei et al, 2015). In the present study, most variables 288 showed no difference between species, with the exception of coverage and total energy.…”
mentioning
confidence: 43%
“…The study by Zölei et al (2015) also 300 suggests that despite the unusually and permanently high parasitism rate found in our study 301 area for at least the last 70-80 years, our host-brood parasite system is in dynamic 302 evolutionary equilibrium, where the ratio of hosts accepting or rejecting parasitic eggs is in 303 equilibrium (Lotem & Nakamura, 1998), and the recognition error rate is low (Stokke et al …”
Section: Fig 2) 240mentioning
confidence: 99%
See 2 more Smart Citations